Not just welfare over justice: Ethics in forensic consultation - Candilis, Philip J. (Legal and criminological psychology, 2014)
The ethics of forensic professionalism is often couched in terms of competing individual and societal values. Indeed, the welfare of individuals is often secondary to the requirements of society, especially given the public nature of courts of law, forensic hospitals, jails, and prisons. We explore the weaknesses of this dichotomous approach to forensic ethics, offering an analysis of Psychology's historical narrative especially relevant to the national security and correctional settings. We contend that a richer, more robust ethical analysis is available if practitioners consider the multiple perspectives in the forensic encounter, and acknowledge the multiple influences of personal, professional, and social values. The setting, context, or role is not sufficient to determine the ethics of forensic practice.